TECHNICAL GUIDANCE ON STRENGTHENING THE ROLE OF UMA IN PRESERVING TRADITIONS AND CULTURE OF MENTAWAI COMMUNITY FOR MENTAWAI STUDENTS IN WEST SUMATRA - Sabagalet, Yudas; Zulfa, Zulfa; Arjun, Arjun; Marco, Marco (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2024)
This community service activity involves Mentawai students throughout West Sumatra. The partner's problem until now is that almost all Mentawai students do not understand their identity and Uma as a sacred Mentawai building is not understood by Mentawai students. The limited knowledge of partners regarding the identity of the Mentawai Community and Uma as an effort to preserve traditions and culture for the younger generation in Mentawai. The purpose of this service is to conduct socialization about the unique and profound cultural identity, which is reflected in their language, beliefs, social systems, and arts and traditions, especially about Uma. The methods used are: providing solutions in order to overcome partner problems. Through needs analysis, work plans, activity implementation, and evaluation. The results of this service are as follows: exploring how the identity of the Mentawai community is formed and maintained in the context of social change, globalization, and the influence of religion and modernization. The results of this service are an increase in the understanding of Mentawai students throughout West Sumatra regarding the importance of this technical guidance so that efforts to have a strong customary system, as well as a close relationship with nature, the Mentawai community faces challenges in maintaining their cultural heritage amidst technological developments and migration. This socialization also discusses the efforts made by the community, government, and NGOs in preserving Mentawai cultural and language values. Thus, this service not only provides insight into the identity of the Mentawai community, but also highlights the importance of preserving culture in a changing global context.